Isolasi dan Identifikasi Bakteri Asam Laktat dari Hasil Fermentasi Limbah Organik Kulit Buah (Eco-Enzyme) - Linda Syafitri Siagian; Kartika Manalu; Rizki Amelia Nasution (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is the isolation and identification based on the morphological characteristics of lactic acid bacteria in the fermentation of organic waste from fruit peels. Isolation of Lactic Acid Bacteria was carried out using the spread plate method on de Man, Rogosa, and Sharpe Agar (MRSA) media. The culture was incubated at 37 °C for 48 hours. The growing colonies were observed for morphological characteristics, and bacterial Gram staining was carried out. The results of the research showed that 10 bacterial isolates were obtained from the isolation of BAL from ecoenzymes on de Man, Ragosa, and Sharpe Agar (MRSA) media, namely E-BAL 01, E-BAL 02, E-BAL O3, E-BAL 04, E-BAL 05, E-BAL 06, E-BAL 07, E-BAL 08, E-BAL 09, and E-BAL 10, and 10 isolates were characterized as Gram-positive with a bacillary cell form. In conclusion, 10 isolates were found with characteristics that supported MRSA media, namely isolates of lactic acid bacteria of the genus Lactobacillus. This is confirmed by the results of biochemical tests, namely that it is immobile, does not produce the catalase enzyme, and does not have the ability to produce gas. Keywords: Lactic Acid Bacteria (LAB), Ecoenzymes, Fruit Skin